Analisis Edukasi Konvensional Kelas Ibu Balita Dengan Metode Digital Micro Learning Berbasis Video Interaktif Terhadap Perawatan Tali Pusat Di Desa Binaka Wilayah Kerja UPTD Puskesmas Gunungsitoli Idanoi - Cahayani Bawaulu; Hadirmanwati Gea; Fani Gea; Indrawati Waruwu; Wiyola Yolanda; Debora Paninsari (Journal of Pharmaceutical and Sciences, 2026)
Background: The high rate of umbilical cord care practices that do not follow standards is influenced by cultural Background: The high rate of umbilical cord care practices that do not follow standards is influenced by cultural factors, limited knowledge among mothers and families, restricted access to health services, and home births assisted by traditional birth attendants. Objective: To analyze the comparison between conventional mother-toddler class education and interactive video-based digital micro learning methods on umbilical cord care. Methods: This study used a quasi-experimental design with two groups (posttest-only non-equivalent control group design). The population consisted of 22 mothers with infants aged 0–7 days in Binaka Village, selected through purposive sampling. Data collection instruments included questionnaires and a checklist sheet. Data analysis used an independent t-test. Results: Statistical analysis showed a p-value of 0.039, which is less than the significance level α (0.05), indicating a significant difference between conventional Mother-Toddler Class education and interactive video-based digital micro learning methods on umbilical cord care. Conclusion: Interactive video-based digital micro learning can be considered an alternative or even a more effective strategy for providing education to mothers of newborns. Healthcare providers, particularly midwives and nurses, can integrate interactive digital media into educational programs to enhance mothers' understanding and skills in umbilical cord care.